PENGARUH KINERJA LINGKUNGAN, STRUKTUR MODAL, DAN KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR ENERGI DI BURSA EFEK INDONESIA TAHUN 2022-2024 - Rafly Fachrurroji; Hermi Hermi (STMIK Widuri Jakarta, 2025)
The energy sector faces high environmental risks and increasing public scrutiny regarding sustainability practices. These conditions highlight the importance of efficient financing strategies and strong corporate governance to enhance firm value. This study aims to examine the effect of environmental performance, capital structure, and managerial ownership on firm value. The research was conducted on energy sector companies listed on the Indonesia Stock Exchange for the 2022–2024 period. Data were collected from annual reports and sustainability reports, then analyzed using panel data regression with a Fixed Effect Model approach. The results show that capital structure has a positive effect on firm value. In contrast, environmental performance and managerial ownership do not show a significant effect. These findings imply that an appropriate financing strategy plays a vital role in increasing firm value. Meanwhile, improving environmental performance and managerial ownership remains essential to strengthen long-term sustainability and corporate governance.